Money, interest rates, and exchange rates with endogenously segmented asset markets - Alvarez, Fernando 1964-; Atkeson, Andrew 1961-; Kehoe, Patrick J. (NBER working paper series, 2000)
This paper analyzes the effects of money injections on interest rates and exchange rates in a model in which agents must pay a Baumol-Tobin style fixed cost to exchange bonds and money. Asset markets are endogenously segmented because this fixed cost leads agents to trade bonds and money only infrequently. When the government injects money through an open market operation, only those agents that are currently trading absorb these injections. Through their impact on these agents' consumption, these money injections affect real interest rates and real exchange rates. We show that the model generates the observed negative relation between expected inflation and real interest rates. With moderate amounts of segmentation, the model also generates other observed features of the data: persistent liquidity effects in interest rates and volatile and persistent exchange rates. A standard model with no fixed costs can produce none of these features.